Evaluasi Implementasi Program E-Kinerja dalam Mendukung Upaya Reformasi Birokrasi di Pemerintah Kota Madiun - Shahwa Al-Sofwa (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The E-Kinerja Program is a policy innovation developed by the Madiun City Government to support the digitalization of civil servant performance management as part of bureaucratic reform and the implementation of the Electronic-Based Government System (SPBE). This study aims to evaluate the implementation of the E-Kinerja Program in Madiun City using six policy evaluation criteria proposed by William N. Dunn, namely effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. This research employs a qualitative descriptive approach, with data collected through interviews, direct observation of the E-Kinerja application usage, and documentation review of related policies. The findings indicate that the E-Kinerja Program is relatively effective and efficient in supporting the monitoring of civil servant attendance and daily activities through features such as QR Code-based attendance, photo documentation, and daily activity reporting. However, several challenges remain, including unstable GPS accuracy, limited internet connectivity, and the practice of non real time input of daily activities. In addition, differences in digital literacy levels and device compatibility among civil servants affect the equitable utilization of the application. Overall, the implementation of the E-Kinerja Program is considered appropriate as part of bureaucratic digital transformation in Madiun City, although further improvements in technical aspects and human resource capacity are required to optimize its implementation.